POTENSI MAKAM SYECH BURHANUDDIN SEBAGAI OBJEK WISATA ZIARAH DI KABUPATEN PADANG PARIAMAN - Selvi, Yuliana; Kasmita, Kasmita; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research arouse from the observation of the researcher when visiting the Object of the Pilgrimage tourist object of the Tomb of Syech Burhanuddin in Padang Pariaman District, that the unknown attraction, narrow accessibility, inadequate existing facilities of tourism and tourism activities contained in the tourist attraction of the Tomb of Syech Burhanuddin. This research is purposedto analyze how the potential of the grave of Syech Burhanuddin as a pilgrimage tourism object in Padang Pariaman Regency which seen from four potential indicators, namely attraction, accessibility, amenities, and activity. This research type is descriptive research with quantitative and qualitative method (mix metdhod). Data collection technique is done by using interview method, observation, documentation, and questionnaire. In this research using Purposive Sampling. Data collection techniques were conducted by interviewing the managers and distributing questionnaires using Guttman scale that has been tested for its validity and reliability.The results of this study found that the overall potential of the Tomb of Syech Burhanuddin as a Pilgrimage Tourism Object In Padang Pariaman District seen from four potential indicators of attraction, accessibility, amenitas, and activity. According to tourists 65.75% are tourist attractions are quite good, 68.75% accessibility is good enough, 44% amenitas not good, and 77% good enough activity.Keywords: Potential, Tourist Attraction